The association of carotid intima-media thickness with body mass index and cortisol level in fibromyalgia syndrome - Koca, Tuba Tülay; Çimen, Ayla (The European Research Journal, 2019)
Objectives: Patients with fibromyalgia syndrome (FMS) may have the risk for atherosclerotic disease because of chronic stress, disrupted neuroendocrine axis, high BMI and inflammation. This is study aimed to research the stress and the stress-related diseases in patients with FMS by measuring obesity, morning serum cortisol level, and carotid intima-media thickness (CIMT), which is the early indicator of the atherosclerosis. Methods: This case-control study included 57 patients who were diagnosed with FMS according to 2010 American College of Rheumatology (ACR) Criteria and visited the outpatient clinic in February 2016. As a control group, 36 healthy females who visited the outpatient clinic in the same month were included. Carotid intima-media thickness and cortisol levels were analysed. Results: The present study included 93 females between 15 and 79 years old. The mean age of the 57 females with FMS and 37 healthy females was 44.5 ± 10.6 years and 47.9 ± 18.5 years, respectively (p = 0.260). The mean CIMT value of the FMS and control groups was 0.64 ± 0.17 mm and 0.59 ± 0.16 mm, respectively (p = 0.170). The morning blood cortisol level in the FMS and control groups was 7.8 ± 3.3 ng/dL and 8.7 ± 2.8 ng/dL, respectively (p = 0.460). The CIMT and morning blood cortisol level were not correlated in the FMS group. Conclusion: According to the present study, CIMT value and morning blood cortisol level were not found significantly different in FMS group, and also were not found correlated with each other.